"Drug‐Carrier" Synergy Therapy for Amyloid‐β Clearance and Inhibition of Tau Phosphorylation via Biomimetic Lipid Nanocomposite Assembly. Issue 14 (20th March 2022) - Han, Guochen; Bai, Kaiwen; Yang, Xiaoyu; Sun, Chenhua; Ji, Yi; Zhou, Jianping; Zhang, Huaqing; Ding, Yang
Abstract: Amyloid‐ β (A β ) toxicity is considered to be companioned by Tau phosphorylation in Alzheimer's disease (AD). The clinical AD therapy is usually subjected to low blood‐brain barrier (BBB) penetration and complex interaction mechanisms between A β and phosphorylated Tau. A "Drug‐Carrier" synergy therapy is herein designed to simultaneously target A β and Tau‐associated pathways for AD treatment. To imitate natural nanoparticle configuration, the endogenous apolipoprotein A‐I and its mimicking peptide 4F fused angiopep‐2 (Ang) are sequentially grafted onto lipid nanocomposite (APLN), providing liberty of BBB crossing and microglia targeted A β clearance. For synergy treatment, methylene blue (MB) is further assembled into APLN (APLN/MB) for Tau aggregation inhibition. After intravenous administration, the optimized density (5 wt%) of Ang ligands dramatically enhances APLN/MB intracerebral shuttling and accumulation, which is 2.15‐fold higher than that Ang absent‐modification. The site‐specific release of MB collaborates APLN to promote A β capture for microglia endocytosis clearance and reduce p‐Tau level by 25.31% in AD pathogenesis. In AD‐A β –Tau bearing mouse models, APLN/MB can relieve AD symptoms, rescue neuron viability and cognitive functions. Collectively, it is confirmed that "Drug‐Carrier" synergy therapy of APLN/MB is a promising approach in the development of AD treatments. Abstract : Clinical Alzheimer's disease (AD) treatment faces dilemmas in low blood‐brain barrier (BBB) penetration and complex interaction mechanisms between A β deposits and phosphorylated Tau. This study provides a biomimetic lipid nanocomposite (APLN/methylene blue) with high BBB penetration for AD therapy via a "Drug‐Carrier" synergy strategy, of which carrier for A β clearance and drug for inhibition of phosphorylated Tau.